Entanglement and spectra in topological many-body localized phases - Decker, K. S. C.; Kennes, D. M.; Eisert, Jens; Karrasch, Christoph (Physical Review B, 2020)
Many-body localized systems in which interactions and disorder come together defy the expectations of quantum statistical mechanics: In contrast to ergodic systems, they do not thermalize when undergoing nonequilibrium dynamics. What is less clear, however, is how topological features interplay with many-body localized phases as well as the nature of the transition between a topological and a trivial state within the latter. In this paper, we numerically address these questions using a combination of extensive tensor network calculations, specifically density matrix renormalization-group-X, as well as exact diagonalization, leading to a comprehensive characterization of Hamiltonian spectra and eigenstate entanglement properties.
CRIS-Team Scopus Importer:2023-04-20